The GMZ2 malaria vaccine: from concept to efficacy in humans. (2nd September 2017) - Theisen, Michael; Adu, Bright; Mordmüller, Benjamin; Singh, Subhash
ABSTRACT: Introduction : GMZ2 is a recombinant protein consisting of conserved domains of GLURP and MSP3, two asexual blood-stage antigens of Plasmodium falciparum, and is designed with the aim of mimicking naturally acquired anti-malarial immunity. The rationale for combining these two antigens is based on a series of immune epidemiological studies from geographically diverse malaria endemic regions; functional in vitro studies; and pre-clinical studies in rodents and New World monkeys. GMZ2 adjuvanted with alhydrogel® (alum) was well tolerated and immunogenic in three phase 1 studies. The recently concluded phase 2 trial of GMZ2/alum, involving 1849 participants 12 to 60 month of age in four countries in West, Central and Eastern Africa, showed that GMZ2 is well tolerated and has some, albeit modest, efficacy in the target population. Areas covered : PubMed (www.ncbi.nlm.nih.gov/pubmed ) was searched to review the progress and future prospects for clinical development of GMZ2 sub-unit vaccine. We will focus on discovery, naturally acquired immunity, functional activity of specific antibodies, sequence diversity, production, pre-clinical and clinical studies. Expert commentary : GMZ2 is well tolerated and has some, albeit modest, efficacy in the target population. More immunogenic formulations should be developed.